The Impact of Preoperative Risk on the Association between Hypotension and Mortality after Cardiac Surgery: An Observational Study - Vanja Ristovic (Journal of Clinical Medicine, 2020)
Background: Despite steady improvements in cardiac surgery-related outcomes, our understanding of the physiologic mechanisms leading to perioperative mortality remains incomplete. Intraoperative hypotension is an important risk factor for mortality after noncardiac surgery but remains relatively unexplored in the context of cardiac surgery. We examined whether the association between intraoperative hypotension and in-hospital mortality varied by patient and procedure characteristics, as defined by the validated Cardiac Anesthesia Risk Evaluation (CARE) mortality risk score. Methods: We conducted a retrospective cohort study of consecutive adult patients who underwent cardiac surgery requiring cardiopulmonary bypass (CPB) from November 2009–March 2015. Those who underwent off-pump, thoracic aorta, transplant and ventricular assist device procedures were excluded. The primary outcome was in-hospital mortality. Hypotension was categorized by mean arterial pressure (MAP) of <55 and between 55–64 mmHg before, during and after CPB. The relationship between hypotension and death was modeled using multivariable logistic regression in the intermediate and high-risk groups. Results: Among 6627 included patients, 131 (2%) died in-hospital. In-hospital mortality in patients with CARE scores of 1, 2, 3, 4 and 5 was 0 (0%), 7 (0.3%), 35 (1.3%), 41 (4.6%) and 48 (13.6%), respectively. In the intermediate-risk group (CARE = 3–4), MAP < 65 mmHg post-CPB was associated with increased odds of death in a dose-dependent fashion (adjusted OR 1.30, 95% CI 1.13–1.49, per 10 min exposure to MAP < 55 mmHg, p = 0.002; adjusted OR 1.18 [1.07–1.30] per 10 min exposure to MAP 55–64 mmHg, p = 0.001). We did not observe an association between hypotension and mortality in the high-risk group (CARE = 5). Conclusions: Post-CPB hypotension is a potentially modifiable risk factor for mortality in intermediate-risk patients. Our findings provide impetus for clinical trials to determine if hemodynamic goal-directed therapies could improve survival in these patients.